The Effect of Competence Work Motivation and Nurse Quality On The Inpatient Service Quality At Bandung Adventist Hospital - Jacqueline Makanoneng; Rudianto Rudianto; Sediatmoko Sediatmoko; Marisi Pakpahan; Mardi Siswoyo (International Forum of Researchers and Lecturers, 2024)
Increasingly tight hospital competition forces hospital management to continue to improve the quality of service, inpatient installation is a facility used by patients for more than 24 hours, so it will greatly affect patient satisfaction, therefore it is important for hospitals to ensure that nurse competence, and Nurse Quality who get work motivation can help hospitals to improve the quality of service. This study aims to analyze the effect of competence, work motivation and Nurse Quality partially and simultaneously on the quality of service. This study uses a quantitative analysis method conducted on 74 nurses at the Inpatient Installation of Advent Hospital Bandung in September 2024, data was collected using a questionnaire that had been tested for validity and reliability which was then processed using SPSS software. The results of this study indicate that partially and simultaneously nurse competence, work motivation and Nurse Quality have a significant and positive effect on the quality of service at the Inpatient Installation of Advent Hospital Bandung.